Converting pseudocode into Python functions (greedy techniques) - Liew, Evangeline (Nanyang Technological University, 2024)
In current studies of data structure algorithms, most of the classes are taught in terms of pseudocode with no real-world context. With such a structure, students would need more insight into understanding why data structure analysis (DSA) is important. With the lack of real-world context, students may not be able to utilize what they have picked in the course.